Effect of Feeding Straw Based Densified Complete Feed Blocks Containing Dhanwantharam Oil Residue and Tapioca Starch Waste on Body Weight, Dry Matter Intake, Feed Conversion Efficiency and Nutrient Digestibility in Crossbred Heifer Calves - Gowda, H.S Sunil; Purushothaman, Sajith; Ally, K.; Ananth, Deepa; Simon, Shibu (Indian Journal of Animal Nutrition, 2020)
The study was carried out to evaluate the effect of feeding straw based densified complete feed blocks containing dhanwantharam oil residue and tapioca starch waste on body weight, dry matter intake, feed conversion efficiency and nutrient digestibility in crossbred heifer calves. Eighteen healthy crossbred heifer calves of eight to twelve months of age were selected from University Livestock Farm and Fodder Research Development Scheme (ULF&FRDS), Mannuthy. The calves were divided into three groups of six each as uniformly as possible with regard to age, sex and body weight and each animal was allotted randomly to one of the three dietary treatments T1 (straw based DCFB), T2 (DCFB containing 20 per cent dhanwantharam oil residue) and T3 (DCFB containing 20 per cent tapioca starch waste) were formulated according to ICAR (2013) standards. Feeding trial lasted for 90 days. A digestion trial of five days duration was conducted to assess nutrient digestibility. Average daily weight gain, dry matter intake and feed conversion efficiency did not differ in crossbred calves of different groups. The digestibility of DM, CP, EE, CF, NFE, NDF and ADF did not differ among the groups. Based on the present study, feeding of straw based densified complete feed blocks containing dhanwantharam oil residue and tapioca starch waste are beneficial in terms of body weight gain, feed intake, nutrients digestibility and feed conversion efficiency in crossbred heifer calves and results were comparable to the control group fed with DCFB containing conventional ingredients. The cost of feeding in group fed with DCFB containing dhanwanthram oil residue was significantly reduced than control group fed with conventional feed blocks.